The Excess Electron in a Boron Nitride Nanotube: Pyramidal NBO Charge Distribution and Remarkable First Hyperpolarizability - Zhong, Rong-Lin; Xu, Hong-Liang; Sun, Shi-Ling; Qiu, Yong-Qing; Su, Zhong-Min (Chemistry : a European journal, 2012)
The unusual properties of species with excess electrons have attracted a lot of interest in recent years due to their wide applications in many promising fields. In this work, we find that the excess electron could be effectively bound by the B atoms of boron nitride nanotube (BNNT), which is inverted pyramidally distributed from B‐rich edge to N‐rich edge. Further, Li@B‐BNNT and Li@N‐BNNT are designed by doping the Li atom to the two edges of BNNT, respectively. Because of the interaction between the Li atom and BNNT, the 2s valence electron of Li becomes a loosely bound excess electron. Interestingly, the distribution of the excess electron in Li@N‐BNNT is more diffuse and pyramidal from B‐rich edge to N‐rich edge, which is fascinating compared with Li@B‐BNNT. Correspondingly, the transition energy of Li@N‐BNNT is 0.99 eV, which is obviously smaller than 2.65 eV of Li@B‐BNNT. As a result, the first hyperpolarizability (3.40×104 a.u.) of Li@N‐BNNT is dramatically larger (25 times) than 1.35×103 a.u. of Li@B‐BNNT. Significantly, we find that the pyramidal distribution of the excess electron is the key factor to determine the first hyperpolarizability, which reveals useful information for scientists to develop new electro‐optic applications of BNNTs. Pyramidal charge distribution: The excess electron in Li@N‐BNNT is pyramidally distributed in the B‐clusters from B‐rich edge to N‐rich edge, whereas the excess electron in Li@B‐BNNT is inverted pyramidally distributed (see figure). Significantly, the transition energy of Li@N‐BNNT is much smaller because the excess electron is more diffuse. As a result, the static first hyperpolarizability (β0) of Li@N‐BNNT is dramatically larger than that of Li@B‐BNNT.